Nonsurgical Elementary Rhinoplasty: A Volumetric Standardized Hyaluronic Acid Filling Technique in Five Steps - Luddi L. Oliveira; André Braz; Eliandre Palermo; Maria C.A. Issa (Indian Journal of Plastic Surgery)
Hyaluronic acid filling to correct the nose contour has gained popularity in recent years. Although many techniques are described about the amount of the product and steps to follow to obtain, practitioners still need clarification about the amount of product and steps to follow obtain natural and safe results. We aim to demonstrate a new technique with a systematic sequence that considers the anatomy and individual characteristics. The nonsurgical elementary rhinoplasty (NOSER) technique is performed in five steps using cannulas, a high G prime hyaluronic acid, and two injection entry points. The areas to be treated and the specific quantity of filler to be used are based on the assessment. Steps 1 to 3 are for the tip's projection, support and lift, and step 4 is for filling the radix area and straightening the dorsum. Step 5 is used for refinement and softening of the supratip. All five steps are done in small aliquots in the central area, at the deep plane. Through the procedure, it is possible to achieve an aesthetic improvement in the nose by widening the labial columellar angle, exposing the columella, projecting the tip, and aligning the dorsum (disguising the hump), even without performing all five steps. This technique could be a good and highly reproducible alternative for upgrading the nose contour.